The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1017/s0033291700038976
|View full text |Cite
|
Sign up to set email alerts
|

The ability of trainee general practitioners to identify psychological distress among their patients

Abstract: SynopsisIt is argued that a general practitioner's ability to make accurate ratings of psychological distress is partly determined by the rate at which patients emit cues that are indicative of such distress. This study addresses the behaviours of doctors which influence the rates at which patients emit such cues. Consultations were videotaped involving six General Practice Vocational Trainees, three of them poor, and three of them able identifiers of emotional illness. Consultations were selected so that each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
11

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 10 publications
3
81
0
11
Order By: Relevance
“…First any screening instrument by definition, will have imperfect sensitivity and specificity itself, although there have been at least 6 studies showing that both of these are very good for the GHQ. There is no true gold standard against which to assess the clinician's ability to detect psychiatric morbidity, but (Goldberg et al, 1993) provide an example of how the GHQ12 has been used successfully in studies aimed at helping general practitioners to identify distress in their patients. Similarly the GHQ28 was used to evaluate physicians' skills in reducing patients' distress in an RCT of a training intervention in the US (Roter et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First any screening instrument by definition, will have imperfect sensitivity and specificity itself, although there have been at least 6 studies showing that both of these are very good for the GHQ. There is no true gold standard against which to assess the clinician's ability to detect psychiatric morbidity, but (Goldberg et al, 1993) provide an example of how the GHQ12 has been used successfully in studies aimed at helping general practitioners to identify distress in their patients. Similarly the GHQ28 was used to evaluate physicians' skills in reducing patients' distress in an RCT of a training intervention in the US (Roter et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This instrument has high internal reliability and validity and was designed specifically as a brief screening instrument in large population studies (Goldberg and Williams, 1988). A conventional scoring method was employed with a threshold of 4 or more indicating probable caseness for psychological morbidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific strategies to explore emotionality may be required if consultants are to tailor their behaviour accordingly. (Goldberg et al, 1993;Maguire et al, 1996). Improving this aspect of consultants' behaviour may be important as it has been shown to have an impact on patient outcomes in medical consultations (Bertakis et al, 1991).…”
Section: Do Consultants Tailor the Consultation According To Demograpmentioning
confidence: 99%
“…For instance, Davenport et al [5] showed that doctors who are better able to detect psychiatric illness are more likely to allow patients to express verbal cues. Subsequent studies [18] '. A cue has been defined as: 'a hint, which might be an expression or signal, mostly verbal but also nonverbal, which indirectly indicates an issue of presumed importance for the patient and implies an emotion, worry or uncertainty that the patient would like to bring up, or a move to another topic, that should demand an exploration from the provider'.…”
Section: Introductionmentioning
confidence: 98%